Loan interest rate Nash models with solvency constraints in the banking sector. (3rd September 2021) - Battulga, G.; Altangerel, L.; Battur, G.
ABSTRACT: This paper attempts to study loan interest rate Nash game models in the banking sector under regulatory solvency constraints. By taking solvency constraints as Basel I, Basel II, and Expected Shortfall (ES), we obtain results regarding the existence of loan interest rate equilibrium. A sensitivity analysis for solvency models and some numerical results are presented. Numerical results show that the weighted loan interest rate of the Mongolian banking system is consistent with the base case of the theoretical weighted loan interest rate corresponding to the Nash equilibrium.